Efficient Synthesis of Isobenzofuran-1(3H)-ones (Phthalides) and Selected Biological Evaluations - Bayer, Ernst; Hayat, Safdar; Rahman, Atta-ur-; Choudhary, M. Iqbal; Khan, Khalid Mohammed; Shah, Syed Tasadaque Ali; Imran-ul-Haq, M.; Anwar, M.Usman; Voelter, Wolfgang (Arzneimittelforschung, 2005)
The studies presented here deal with the convenient and efficient one-step conversion of o-alkylbenzoic acids into their corresponding isobenzofuran-1(3H)-ones (phthalides) using NaBrO3/NaHSO3 in a two-phase system. A range of o-alkylbenzoic acids was used with the object of getting a variety of phthalide derivatives as multipurpose biologically active compounds. Seventeen phthalides have been synthesized and tested for cytotoxicity, antibacterial and antifungal activities. Some of these compounds showed promising cytotoxic effects against Artemia salina. Compounds 4j-4p were highly active against Gram-negative and Grampositive bacteria among all tested compounds. In the fungicidal assay, the compounds showed a broad spectrum of activity against six fungi. All compounds were characterized via elemental analysis, UV, IR, mass and-NMR spectroscopy.
Keywords: Isobenzofuran-1(3H)-ones, bactericidal activity, cytotoxicity, fungicidal activity; Phthalides